Vocabulary Mastery Through KAKI SI KOKA Media for Elementary School Students - Ariyanti, Nofa; Kironoratri, Lintang; Amaliyah, Fitriyah (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This study aimed to describe the improvement of students' vocabulary mastery by using a team game tournament model assisted by KAKI SI KOKA media in Indonesian subjects. The research method used is classroom action research (PTK), which has two cycles. Each Cycle consists of planning, implementation, observation, and reflection. This research was conducted in SD 4 Karangrowo grade IV with 33 students. Data collection techniques include interviews, observations, tests, and documentation. The data analysis used is quantitative and qualitative. The results of the study using the TGT model assisted by the media KAKI SI KOKA can increase Vocabulary in Indonesian subjects in grade IV SD 4 Karangrowo, as evidenced by the completion of 20 students with a percentage of 60.6% in the first Cycle, which has increased but has not been maximized, so it is necessary to be disciplined II, after the implementation of cycle II, the results of student vocabulary mastery increased with 27 students experiencing completeness with a percentage of 81.81%. Based on classroom action research, using KAKI SI KOKA media can increase students' vocabulary mastery at SD 4 Karangrowo. Applying KAKI SI KOKA learning media makes students more active and creative in Learning.